Approush to specific diagnostics of causative agents of infectious endocardidis - Katsapov, D (Annals of Mechnikov’s Institute, 2020)
Introduction. Increased level of morbidity of infective endocarditis (IE) connected with new risk factors: intravenous drug use, cardiosurgical interventions, hemodialysis brought new clinical forms of the disease. As it shown in a literature main pathogenetic factors of IE are bacteraemia, trauma of endocardium and invasive medical procedures. Very typical pathogens are streptococci and staphylococci. Most typically mitral and aortal valves are affected with spreading of vegetations on surrounding media. Discussion. IE is polyetiologic disease caused by more than 128 microorganisms, and still a challenge for medical professionals. Detection a causative agent is critical for proper specific treatment. In different sources data on percentage of proven cases very according to country and different medical centres reflecting different local epidemiology of IE, diagnostic criteria and protocols. Culture negative infectious endocarditis (CNIE) is considered in case of obtaining of three negative results of cultivation of samples on a standard blood agar during 7 days and subculturing. CNIE incidence very form 2% to 33% according to different researches and higher in cases of community acquired infection and reseeding antibacterial treatment. Some of cases of CNIE caused by gram - negative fastidious microorganisms - Haemophilus parainfluenzae, Actinobacillus, Actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, Kingella kingae, with united in HACEK group according to their properties to colonize oropharynx and requirement in special conditions and duration of incubation. Detection of some intracellular bacteria, such as C. burnetti and Bartonella spp. require immunological methods of detection, histological methods and of PCR. Conclusion. In case of diagnostics of patients with CNIE it is necessary to use a combination of prolonged subculturing of serum, emboli and histologic material on blood agar with microscopy by Warthin-Starry, Gimenez and PAS with serologic methods and broad - range PCR amplification.